2004
DOI: 10.1002/cncr.20367
|View full text |Cite
|
Sign up to set email alerts
|

Transjugular intrahepatic portosystemic shunts: Experience in the oncology setting

Abstract: BACKGROUNDTransjugular intrahepatic portosystemic shunt (TIPS) placement has emerged as an effective and minimally invasive method of treating portal hypertension and its associated complications. To the authors' knowledge there is limited documentation of its use for percutaneous shunting in patients with hepatic and extrahepatic malignancies. The current study reports the authors' experience with TIPS in the oncology setting.METHODSThirty‐eight patients with cancer underwent TIPS procedures. Nineteen patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 42 publications
5
19
2
1
Order By: Relevance
“…27 We also observed a similar rate of post-TIPSS HE with 40.0%. One of these patients developed severe grade IV HE and died of multiorgan failure.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…27 We also observed a similar rate of post-TIPSS HE with 40.0%. One of these patients developed severe grade IV HE and died of multiorgan failure.…”
Section: Discussionsupporting
confidence: 79%
“…Wallace et al reported a 30-day survival rate of 84%. 27 Our data even showed a rate of 97.5%. This high 30-day survival rate can be explained by strict selection for TIPSS implantation in our patient cohort.…”
Section: Discussioncontrasting
confidence: 45%
See 3 more Smart Citations